Examining the changing nature of stress: stress of working from home during pandemic crisis - Liew, Amanda Li Shiuen; Wong, Siew Chin; Lim, Chui Seong; Mohd Rasdi, Roziah (Sage Publications, 2022)
The purpose of this study is to examine the relationship among social isolation, lack of facility provision, family commitment and work from home (WFH) job stress among academicians. Data were collected from 180 respondents who were academicians who worked from home during the period of movement control order (MCO) owing to the spread of COVID-19 pandemic. Partial least square structural equation modelling (PLS-SEM) was used to analyse the data collected. The results show that all predictors, namely social isolation, lack of facilities provision and family commitment are statistically correlated to WFH job stress. The empirical findings provide additional insights in order to improve the understanding of the existing model of stress and practical implications for academicians, educational institutions/schools and the government in order to reduce/address WFH job stress effectively. In addition, the study seeks to enhance awareness and destigmatize the mental health issues of academicians due to the changes in the nature of the job, which is important to help them to maintain a healthy well-being during the pandemic crisis.